Building information modeling acceptance and readiness assessment in Taiwanese architectural firms - Juan, Yi-Kai; Lai, Wan-Ying; Shih, Shen-Guan (Journal of Civil Engineering and Management, 2017)
Building information modeling (BIM) has received considerable recognition in the architecture, engineering, and construction (AEC) industry because it can potentially reduce costs and delivery time and improve quality. Conscious of the benefits derived by adopting BIM, the Taiwanese government is planning to enact a policy that would incorporate BIM-based e-submission into the Taiwanese building permit review process, revolutionizing the local AEC industry. Nevertheless, the effects of BIM application are unpredictable. The aim of this study was to investigate the current status of BIM adoption in 224 Taiwanese architectural firms, assess how accepting and ready the firms were to implement BIM, and create a predictive model that can be used by decision makers who are considering adopting BIM. The results revealed that approximately one-third of the firms surveyed had already adopted BIM-based tools. More than half of the firms were willing to use BIM-based tools to streamline the building permit review process; however, their willingness was strongly influenced by governmental policies, competitor motivation, financial incentives, and technological support. The challenges, problems, and opportunities related to adopting BIM were discussed. Lessons learned from the experiences of the Taiwanese firms may be useful to firms facing similar situations and challenges in other countries.First published online: 27 Jun 2016